MEDICO-LEGAL ANALYSIS OF BLOOD LOSS-INDUCED DAMAGE TO SOFT TISSUES AND KIDNEYS - Rakhmanova Mubarak (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. The article discusses the results of an experimental study on modeling mechanical trauma accompanied by damage to soft tissues and the kidney under conditions of blood loss and without it. A certain dynamics of pathomorphological changes was revealed both in soft tissues and in the kidney, depending on the duration of the damage.